(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article describes the relevance of differentiated education in pedagogical higher education institutions, which involves the development of professional skills and competencies in the field, based on the needs for education, in connection with the individual typological characteristics of students. It discusses the importance of multi-level education, which is very widespread in pedagogical practice as one of the important means of preventing and eliminating educational failure. The positive acceptance of the Mannheim educational system in France, Russia, the USA, Belgium and other countries of the world is described. It also provides information on the fact that differentiated education is one of the important factors in the formation of professional motivation of students.